Uji Kuat Tekan Mortar Dengan Substitusi Abu Batu Moramo Pada Campuran Mortar Pasir Halus Sabulakoa: Compressive Strength Test Of Mortar With Moramo Stone Ash Substitution In Sabulakoa Fine Sand Mortar Mixture - Hujiyanto; Irwan Lakawa; Vickky Anggara Ilham (Media Ilmiah Teknik Sipil, 2025)
Mortar mixture is an important element in civil/construction work. As a binding agent, mortar mixtures are widely used in various types of work with different strength levels according to their needs. Many sand raw materials are often used but do not meet the material requirements, either grain gradation or other requirements. In this research, a compressive strength test was carried out using fine sand with the addition of stone ash, to test how much strength was achieved with varying percentages of additional stone ash. The manufacture of test specimens for this mortar mixture refers to SNI 03-6882-2002. Testing was carried out at 7 days, 14 days and 28 days. With additional variations of 0%, 20%, 40% and 60% stone ash. The results of this research are mortar mixtures with the addition of 20% stone ash will increase the compressive strength from 4.74 MPa without the addition of stone ash to 7.13 MPa, tending to decrease at an additional 40% the compressive strength is 6.96 MPa and at an additional 60% the strength is obtained. press 5.74Mpa. The simple regression equation for the relationship between the addition of the percentage of stone ash (variable x) and the compressive strength value (variable y) is y = -22.578x2 + 14.97x + 4.8122 with the coefficient of determination R2 = 0.97 (very strong).